Immobilised Phaeodactylum tricornutum as biomonitor of trace element availability in the water column during dredging - Cabrita, Maria Teresa
This work reports changes of Cr, Cu, Zn, Cd, Hg and Pb concentrations in the dissolved fraction, suspended particulate matter and immobilised Phaeodactylum tricornutum Bohlin (Bacillariophyceae), as well as of microalgae specific growth rates, during a 5-month period dredging operation in a contaminated area of the Tagus estuary, Portugal. Trace element concentrations showed broad variations in the dissolved fraction and suspended particulate matter, presumably reflecting rapid exchanges of redox-sensitive elements between water and particles, in conjunction with the dilution effect caused by the tidal excursion. Immobilised cells exposed to dredging environmental conditions showed significantly higher concentrations of Cr, Cu, Zn, Cd, Hg and Pb than under no dredging conditions. Concomitantly, specific cell growth was significantly lower, suggesting that elements released with dredging affect the microalgae physiology. The results obtained in this in situ work imply that the dissolved fraction and the suspended particulate matter are relatively ineffective indicators of the trace element enhancement during dredging and pointed out immobilised P. tricornutum as a reliable and efficient biomonitoring tool for the assessment of trace element remobilisation.